2011
DOI: 10.1186/1471-2377-11-134
|View full text |Cite
|
Sign up to set email alerts
|

Novel SCARB2 mutation in action myoclonus-renal failure syndrome and evaluation of SCARB2mutations in isolated AMRF features

Abstract: BackgroundAction myoclonus-renal failure syndrome is a hereditary form of progressive myoclonus epilepsy associated with renal failure. It is considered to be an autosomal-recessive disease related to loss-of-function mutations in SCARB2. We studied a German AMRF family, additionally showing signs of demyelinating polyneuropathy and dilated cardiomyopathy.To test the hypothesis whether isolated appearance of individual AMRF syndrome features could be related to heterozygote SCARB2 mutations, we screened for SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 17 publications
(23 reference statements)
2
15
0
Order By: Relevance
“…Immunostaining analyses of brain and kidney samples with an antibody specific for the C‐terminus of SCARB2 (LIMP II) showed that the protein was not severely decreased in case 1 (Figure ). On the other hand, the R121X mutation detected in case 2 (Figure ) was a type similar to those in cases reported previously . Such nonsense mutations generate premature translation termination codons (PTCs) and generally facilitate degradation of SCARB2 mRNA by nonsense‐mediated mRNA decay (NMD).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Immunostaining analyses of brain and kidney samples with an antibody specific for the C‐terminus of SCARB2 (LIMP II) showed that the protein was not severely decreased in case 1 (Figure ). On the other hand, the R121X mutation detected in case 2 (Figure ) was a type similar to those in cases reported previously . Such nonsense mutations generate premature translation termination codons (PTCs) and generally facilitate degradation of SCARB2 mRNA by nonsense‐mediated mRNA decay (NMD).…”
Section: Discussionsupporting
confidence: 76%
“…Finally, dementia (or cognitive decline), which has never been described in patients with AMRF or PME‐SCAB2 , was evident in the present two patients. It is important to note that marked dementia was evident in the final year of life in the 24‐year‐old woman who was diagnosed post mortem as having a ‘pigment variant of neuronal ceroid lipofuscinosis (Kufs' disease)’ .…”
Section: Discussionsupporting
confidence: 59%
“…Another study by Hopfner et al . examined a German family with AMRF, showing that three affected members who were homozygous for the SCARB2 mutation c.111delC also had a demyelinating peripheral neuropathy [65]. …”
Section: Disease Manifestations Associated With Limp-2 Deficiencymentioning
confidence: 99%
“…Two of the affected members of the German AMRF family described by Hopfner et al . developed cardiomyopathy, which may be significant given this important finding, but further analyses are necessary to elucidate this connection [25,65]. …”
Section: Disease Manifestations Associated With Limp-2 Deficiencymentioning
confidence: 99%
“…It is an autosomal-recessive disease related to loss-of-function mutations in SCARB2 gene 14. The onset is in the second and third decades, but there is also a late-onset form, starting in the fifth and sixth decades and without renal failure 15 16.…”
Section: Introductionmentioning
confidence: 99%